2020
DOI: 10.1002/ange.202008207
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphanyl‐Phosphagallene that Functions as a Frustrated Lewis Pair

Abstract: Phosphagallenes (1 a/1 b) featuring double bonds between phosphorus and gallium were synthesized by reaction of (phosphanyl)phosphaketenes with the gallium carbenoid Ga(Nacnac) (Nacnac=HC[C(Me)N(2,6‐i‐Pr2C6H3)]2). The stability of these species is dependent on the saturation of the phosphanyl moiety. 1 a, which bears an unsaturated phosphanyl ring, rearranges in solution to yield a spirocyclic compound (2) which contains a P=P bond. The saturated variant 1 b is stable even at elevated temperatures. 1 b behaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Goicoechea et al . showed the successful synthesis of (Nacnac)‐stabilised phosphanyl‐phosphagallene and demonstrated its reactivity as a frustrated Lewis pair by conversions with H 2 and CO 2 [12] . Furthermore, (Nacnac)EH Pn H 2 (E=Ga, Al, In; Pn =P, As, Sb) and (Nacnac)E( Pn H 2 ) 2 were reported by our own group as well as by the von Hänisch group [13,14] .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Goicoechea et al . showed the successful synthesis of (Nacnac)‐stabilised phosphanyl‐phosphagallene and demonstrated its reactivity as a frustrated Lewis pair by conversions with H 2 and CO 2 [12] . Furthermore, (Nacnac)EH Pn H 2 (E=Ga, Al, In; Pn =P, As, Sb) and (Nacnac)E( Pn H 2 ) 2 were reported by our own group as well as by the von Hänisch group [13,14] .…”
Section: Introductionmentioning
confidence: 72%
“…[11] Goicoechea et al showed the successful synthesis of (Nacnac)-stabilised phosphanyl-phosphagallene and demonstrated its reactivity as a frustrated Lewis pair by conversions with H 2 and CO 2 . [12] Furthermore, (Nacnac)EHPnH 2 (E = Ga, Al, In; Pn = P, As, Sb) and (Nacnac)E(PnH 2 ) 2 were reported by our own group as well as by the von Hänisch group. [13,14] Von Hänisch et al were also able to synthesise neutral 13/(15/14)/13 chain compounds by oxidative addition of (Nacnac)GaHPnH 2 or silyl(di)phosphanes with (Nacnac)Ga. [14,15] In view of tripentelyltrielanes E(PnH 2 ) 3 , however, only tris(dialkylphosphanyl)boranes B(PR 2 ) 3 are known so far, as the strong bonds between phosphorus and boron in combination with bulky organic residues keep the molecules together as monomers despite lacking external stabilisation.…”
Section: Introductionmentioning
confidence: 76%
“…However, with respect to the predominately used d -block elements, main group elements have the advantages of being readily available, inexpensive, and less toxic. Consequently, a variety of the TM-free systems, including the main group multiply bonded compounds, frustrated Lewis pairs (FLPs), group 13 carbene analogues, tetrylenes, , and pnictogen (Pn) compounds, have also been developed to activate dihydrogen, which exhibits TM-like reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphagallenes were synthesised by Goicoechea and Schulz using phosphanyl‐ or gallaphosphaketenes, respectively. Both groups utilized the readily available Ga(I) precursor ( Dip Nacnac)Ga ( Dip Nacnac=HC[C(Me)NDip] 2 ) in conjunction with the phosphaketenes [(S)P]−PCO ([(S)P]=(H n CNDip) 2 P; n=1, 2) or ( Dip Nacnac)Ga(Cl)−PCO facilitating CO cleavage and formation of [(S)P]−P=Ga( Dip Nacnac) ( G , Figure 1), [11] or ( Dip Nacnac)Ga=P−Ga(Cl)( Dip Nacnac) ( H , Figure 1), [12] respectively. Early attempts to generate monomeric phosphagallenes, revealed the formation of the trimeric species [(2,4,6‐Ph 3 ‐C 6 H 2 )GaP c Hex] 3 when (2,4,6‐Ph 3 ‐C 6 H 2 )GaCl 2 was treated with Li 2 P c Hex ( c Hex= cyclo ‐C 6 H 11 ) in a 1 : 1 molar ratio [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphaalumenes C and D were found to react with alkynes, alkenes and butadiene, to give P,Al‐heterocycles and P,Al‐barrelenes, after initial [2+2] cycloaddition reactions at the P−Al double bond. Phosphanylphosphagallenes ( G ), mainly show 1,3‐dipolar reactivity, akin to frustrated Lewis pairs (FLP), towards a range of protic substrates, with the anionic group being added to Ga, while the phosphanyl P atom is protonated [11,19] . H mainly reacts at the P−Ga double bond in 1,2‐additions, [20] and the reversible activation of carbodiimides and CO 2 was reported [21] .…”
Section: Introductionmentioning
confidence: 99%